FAKTOR-FAKTOR YANG MEMPENGARUHI LEMAHNYA EKSPOR TEH INDONESIA KE NEGARA RUSIA (2008-2012) - Marta Sari Uli Pakpahan; Idjang Tjarsono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The position of Indonesia in international trade is one of the largest tea producers and exporters in the world . The role of tea as the raw material for the industry itself is a major contribution to foreign exchange, absorbing a large amount of labor , and the positive impact that makes tea as one of the leading commodity nationwide . Over the last 5 years , tea industry tends to decline including reduced acreage , production decline , and then also have a negative impact on the value of the volume of tea exports to Russia . The purpose of this research was to determine the factors that influence the weak of Indonesian tea exports competitiveness to Russia in 2008-2012. The author uses the theory of comparative advantage by David Richardo and the concept of competitiveness as a baseline research . The method used in this research is descriptive analytical method with a case study approach . The author obtained the data and materials based on books , journals , magazines / newspapers , theses , and websites that related to research. The final results of the research by the authors showed that the weakening of the Indonesian-Russian tea export caused by the Indonesian government policies that are less conducive to the development of a national commodity.Key Word : tea, exports, government, policies.